Replication Data for: The impact of climate change on coffee production in Central America - Bunn, Christian; Lundy, Mark M.; Castro, Fabio (International Center for Tropical Agriculture, 2018)
This data is a series of maps of Central American countries that specify the agro-ecological distribution suitable for coffee cultivation and show the impact gradient by indicating the change of the suitable agro-ecological zones, with the purpose of helping increase the private sector engagement in Climate Smart Agriculture in the region and provide the coffee sector with knowledge needed to facilitate the adoption of CSA practices. The maps were done through a random forest model in which precipitation and temperature were used as drivers and the model was trained through presences and pseudo-absences. (2018-09-07)